5‐3: 3‐Stacked Top‐Emitting White OLEDs with Super‐Wide Color Gamut and High Efficiency. Issue 1 (29th May 2019) - Song, Wenfeng; You, Juanjuan; Wu, Chang-Yen; Wang, Linlin; Shen, Yongqi; Bo, Bin; Quan, Wei; Luo, Chengyuan; Yu, Donghui; Li, Wei; Shih, Huai-Ting; Wu, Zhongyuan
Abstract : A set of top‐emitting OLED with wide‐color gamut and high‐efficiency were successfully fabricated by using 3‐stacked B/RG/B tandem structure and color filter. Optimization of MgAg and Indium Zinc Oxide (IZO) composite structure made the devices with IZO served as capping layer almost identical to the devices with conventional organic capping layer. On the whole, they exhibited 90% color gamut coverage of the ultra‐high definition display standard BT.2020, while maintaining high efficiency of red 15.5 cd/A, green 26.6 cd/A, blue 3.5 cd/A. The impressive properties make them applicable to a variety of occasions, such as the medium‐sized notebook monitors, emerging high‐specification virtual and augmented reality (VR/AR) technologies, and special medical displays.